Investigating esophageal sarcomatoid carcinoma and its comparison with esophageal squamous cell carcinoma on clinicopathological characteristics, prognosis, and radiomics features: a retrospective study - Hu, Binbin; Zhao, Kejia; Yang, Yushang; Zhang, Yi; Liu, Guihong; Zeng, Haiyan; Zou, Bingwen (Frontiers in Oncology, 2024)
Introduction: Esophageal sarcomatoid carcinoma (ESC) is a rare pathological subtype of esophageal carcinomas, wherein its epithelial component typically demonstrates squamous cell carcinoma (SCC).However, the clinicopathological features and prognosis of ESC remain unclear, alongside its unique aspects compared to esophageal SCC (ESCC). Methods: Between January 2008 to December 2018, we retrospectively reviewed 67 ESC patients treated at West China Hospital. Among them, 51 patients with resected ESC were matched with 98 resected ESCC patients over the same period using propensity score matching at 1:2. Survival time and radiomics features of the two groups were compared. Results: A total of 59 patients with resected ESC and 8 patients with non-resected ESC were enrolled. Progression-free survival (PFS) and overall survival (OS) were significant different in patients with different TNM stage (p < 0.001). Multivariate analysis showed that length of tumor was an independent factor for OS in resetable ESC (p = 0.041). Among matched ESC and ESCC patients, OS was significantly longer for patients with ESC than those with ESCC (5-year OS, 61.1% vs. 43.6%; HR 0.59, 95% CI 0.35-0.96; p = 0.032). A rad-score for discriminating ESC from ESCC contained two CT derived radiomic features was developed (area under the curve: 0.823 (95%CI 0.732-0.913) in the training cohort and 0.828 (95% CI 0.636-1.000) in the validation cohort, respectively). Conclusions: ESC has a better prognosis when compared with ESCC. By developing a radiomics prediction model, we provide reliability and convenience for the differential diagnosis of ESC from ESCC.